Experimentation in the business school: a research model - Valdez Cervantes, Alfonso; Franco Valdez, Ana Dolores (Journal of Management and Business Education, 2020)
Educators constantly question themselves how to motivate their students to learn and get them to involve with assignment and their objectives or, in other words, how to encourage them to develop competencies and academic performance. This research demonstrates how experimentation carried out in a laboratory at the business school as a convenience store achieves two academic objectives, the first to develop cognitive and procedural competencies and the second to test a research model in which experiential learning generates higher academic performance by increasing student motivation. Through the collection and analysis of empirical data on the opinion of university graduates, it is possible to test the development of competences and using the regression model 4 of Hayes (2012), the research model is tested. The results provide pertinent information to educators and universities on this teaching methodology to be used to have educational benefits of experiential learning.